Evaluation of the effectiveness and prognostic significance of the use of CMR in determining the viability of the myocardium - Ya. K. Rustamova; V. A. Azizov (Бюллетень сибирской медицины)
Aim: to evaluate the effectiveness of the cardiac magnetic resonance (CMR) method with delayed contrast for the diagnosis of viable dysfunctional myocardium.Materials and methods. А total of 148 patients participated in the analysis of the study. Inclusion criteria: myocardial infarction in past medical history; myocardial ischemia according to stress tests; occlusion or subtotal stenosis of one or more coronary arteries according to digital angiography (SYNTAX score < 32); viable myocardium in the zone of the occluded/stenotic artery; heart failure of I–III functional class (NYHA); left ventricular ejection fraction (LVEF) of less than 50%. Patients were randomized into 2 equivalent groups: in group I, myocardial viability was determined by CMR with delayed contrast, in group II, by stress-echocardiography with dobutamine. All patients underwent stenting of the coronary arteries in the zone of the viable myocardium with drug-eluting stents. Long-term results of treatment were followed 18 months after endovascular intervention in all patients.Results. CMR method with delayed contrasting allows to reliably estimate the existing violations of local contractility in the area of the hibernated myocardium. In patients from group I, it was possible to determine the mass fraction (volume) of the ischemic viable myocardium, which was not possible for patients from group II. Thus, the average indices of the volume of ischemic myocardium were (32.8 ± 2.4)%. All patients had a significant improvement in the local contractility of the myocardium after performed endovascular myocardial revascularization. After 18 months, a significant decrease in the mass fraction of ischemic viable myocardium in the peri-infarction zone was noted among patients from group I, compared with preoperative data ((32.8 ± 2.4) and (20.7 ± 3.1)%, respectively, p < 0.05). Thus, in group I the volume of ischemic myocardium decreased by 37%. In all studied groups, there was a significant increase in LVEF, compared with data obtained when the patient was discharged from the hospital. Survival in group I was 100%, whereas in group II it was 97.3% (p > 0.05). The incidence of non-fatal MI was 1.4 and 8.1% in groups I and II, respectively (p < 0.05).Conclusion. CMR with delayed contrast is more effective and sensitive for diagnosis of myocardial viability and patient prognosis after endovascular intervention, compared with stress echocardiography with dobutamine.